19F NMR for the speciation and quantification of the OH-molecules in complex matrices - Vlasiou, Manolis; Drouza, Chryssoula (My University, 2015)
A novel method for the speciation and quantification of the minor OH-molecules in complex matrices in a one pot experiment based on 19F NMR spectroscopy is demonstrated. The method exerts high resolution and sensitivity comparable with conventional methods and gives reliable results when directly applied to edible oils.
Keywords: OH-molecules; NMR spectroscopy